2011
DOI: 10.4041/kjod.2011.41.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of unilateral buccal crossbite with mandibular symphyseal distraction osteogenesis

Abstract: The aim of this report is to present the treatment of a 14-year-old boy with scissors-bite. Mandibular symphyseal distraction osteogenesis (MSDO) with tooth-supported distractor was performed to expand the mandible, and intermaxillary cross elastics were used. The mandible was expanded approximately 9 mm. Asymmetric widening was done by using cross elastics and MSDO simultaneously. The buccal crossbite was corrected successfully. After a 2-year observation period, widening of the mandible using this procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Although it has several advantages, the surgeon must be careful because it could cause periodontal defects or ankylosis of the involved teeth if excess osseous tissue is removed or injuring the periodontal ligament. This also can cause phonetic problems and TMJ disorders (10) .…”
Section: Mandible Appliancementioning
confidence: 99%
“…Although it has several advantages, the surgeon must be careful because it could cause periodontal defects or ankylosis of the involved teeth if excess osseous tissue is removed or injuring the periodontal ligament. This also can cause phonetic problems and TMJ disorders (10) .…”
Section: Mandible Appliancementioning
confidence: 99%
“…6 Previous case reports have indicated that some patients with unilateral Brodie bite may suffer from temporomandibular joint disorders (TMD) 7 and facial asymmetry. [8][9][10][11][12] The condylar position and morphology were also suggested to be different in several cases of unilateral Brodie bite. 9,10 Accordingly, we hypothesized that unilateral Brodie bite might be correlated with the mandibular morphology and position in patients with unilateral Brodie bite.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that unilateral scissors‐bite can be asymptomatic initially and compromised by chewing on the healthy side 6 . Previous case reports have indicated that some patients with unilateral Brodie bite may suffer from temporomandibular joint disorders (TMD) 7 and facial asymmetry 8–12 . The condylar position and morphology were also suggested to be different in several cases of unilateral Brodie bite 9,10 .…”
Section: Introductionmentioning
confidence: 99%